DEVELOPMENT OF OPTIMAL INVENTORY MANAGEMENT MODELS WITH HYBRID PUSH/ PULL SYSTEM AS INCREASED PERFORMANCE OF FISHERY ENTITIES IN NORTH SULAWESI - Anita Ludia Vivian Wauran; Joseph Nugraha Tangon; Alpindos Toweula (EAJ (Economic and Accounting Journal), 2018)
Proper production and inventory policies are key factors for the success of modern companies in a competitive environment. In order to be a winner and a very high demand, it is very important for the company to overcome the problems of production, timely delivery, and the transfer of which is a limitation or difficult company. There is a need for an optimal management that can manage the resource constraints of a companythrough the theory constrains of a hybrid policy that collaborates between push strategies, which is to make an order by pull strategy, which is to make it stored (David Claudio, Jie Zhang, and Ying Zhang, 2007). The purpose of this research is to produce an optimal management model with hybrid push/pull system as a manifestion of fishery performance in North Sulawesi.The types of data used in this study are qualitative data and quantitative data, qualitative data directly from primary sources of fisheries entities in North Sulawesi through interviews. While quantitative data is obtained from secondary sources is data of corporate financial statements including production reports of Fisheries Entities in North Sulawesi through documents with all the contents of all fisheries entities.